2013
DOI: 10.1371/journal.pone.0059867
|View full text |Cite
|
Sign up to set email alerts
|

Improved Methods for Reprogramming Human Dermal Fibroblasts Using Fluorescence Activated Cell Sorting

Abstract: Current methods to derive induced pluripotent stem cell (iPSC) lines from human dermal fibroblasts by viral infection rely on expensive and lengthy protocols. One major factor contributing to the time required to derive lines is the ability of researchers to identify fully reprogrammed unique candidate clones from a mixed cell population containing transformed or partially reprogrammed cells and fibroblasts at an early time point post infection. Failure to select high quality colonies early in the derivation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 19 publications
(26 reference statements)
2
34
0
Order By: Relevance
“…Building upon our previous work 19 , we employed negative selection against incompletely reprogrammed cells with an immunomagnetic bead separation device (MACS) (Fig. 3a, Supplementary Fig.…”
Section: Automated Ipsc Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Building upon our previous work 19 , we employed negative selection against incompletely reprogrammed cells with an immunomagnetic bead separation device (MACS) (Fig. 3a, Supplementary Fig.…”
Section: Automated Ipsc Purificationmentioning
confidence: 99%
“…To quantitatively assess pluripotency, we automated the spontaneous differentiation of EBs in V-bottom plates and performed a modified version of the previously described stem cell "scorecard" gene expression assay 19,20 to measure propensity for differentiation into the embryonic germ layers (ectoderm, mesoderm and endoderm) relative to hESC EBs ( Fig. 4a,b, Supplementary Fig.…”
Section: Automated Analysis Of Differentiation Propensitymentioning
confidence: 99%
See 1 more Smart Citation
“…For the hESC/ HDF separation experiments, HDF were discriminated from hESCs using an antibody to CD13 (APC-conjugated mouse anti-human CD13, BD Pharmingen TM ; 1:1000 dilution) (Kahler et al, 2013) and an appropriate isotype control. Depletion calculations were based on changes in numbers of CD13-positive cells in the various cell samples (feed, permeate, and retentate) following separations.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…7 More recently, small molecules have been used as an alternative method for reprogramming in the hope of avoiding complications linked to delivering reprogramming factors using viral vectors. Zhang et al 9 and Kahler et al 10 Oral tissues have been shown to be a very useful source of cells that can be targeted for reprogramming to iPSC. Dental pulp stem cells, stem cells from exfoliated deciduous teeth, stem cells from apical papilla, as well as oral mucosal fibroblasts, have all shown a high efficiency of reprogrammed to iPSC.…”
Section: Generation Of Oral Cell Types From Ipsc Sourcesmentioning
confidence: 99%